Burden of Intestinal Parasitic Infections among Children from Five Schools in Bhairahawa, Nepal: A Comparative Cross-Sectional Study - Raut, Shristi; Bhattarai, Srijan; Khanal, Rita; Khatiwada, Sulochana; Kasarla, Rajeshwar Reddy (Journal of Universal College of Medical Sciences, 2021)
INTRODUCTION: Intestinal parasites cause significant morbidity and mortality, particularly in the tropics including Nepal. The main objective of this study was to explore the burden of intestinal parasitic infections among children in 5 different primary schools in Bhairahawa, Nepal. MATERIAL AND METHODS: This was a cross-sectional comparative study among 408 children from 5 schools in Bhirahawa, Nepal. Stool specimens collected in a plastic container were transported to microbiology laboratory in Universal College of Medical Sciences Teaching Hospital (UCMSTH) immediately. Each sample was examined macroscopically and microscopically for the evidence of parasitic infection. All samples were re-analysed by sedimentation and floatation concentration techniques one after another. RESULTS: The overall prevalence of the parasitic infection was 46.5%. The prevalence varied by the methods that included routine microscopy (23.2%), sedimentation (41.6%) and flotation (8.3%). Ascaris lumbricoides was the most common (29.1%) parasite followed by Entamoeba histolytica (6.1%). Mixed infection was also seen in 7.8% of the samples. Factors such as children’s academic year, age, religion, existing illness, household water sources, meat consumed, domestic animals at house, and recent history of taking anti-helminthics were significantly associated with the intestinal parasitic infections. Prevalence of intestinal parasitic infection was higher in public school (61.1%) compared to private school (37%). Male students had slightly more infections (47.3%) than females (45.7%). CONCLUSIONS: Enteric parasitic infection was very high among the primary schools’ students in Bhairahawa, Nepal. Integrating concentration techniques in routine test can help to detect most of the enteric parasites in stool specimens.